Behavioural flexibility in a heat-sensitive endotherm: the role of bed sites as thermal refuges. (August 2021) - Verzuh, Tana L.; Hall, L. Embere; Cufaude, Teal; Knox, Lee; Class, Corey; Monteith, Kevin L.
Abstract : As the climate warms, endotherms are challenged with maintaining body temperature within a neutral range. Modifying behaviour to mitigate heat loads is a potentially low-cost response to avoid heat stress and may be critical to persistence in a changing environment, especially for large endotherms. We tested the hypothesis that bed sites are a thermal refuge and means of behavioural mitigation of heat loads for a large temperate ungulate especially prone to heat stress, the Shiras moose, Alces alces shirasi . We predicted that if bed sites are a thermal refuge, selection of bed sites should be consistent with sites that reduce heat gain or increase heat loss via convection or conduction. Moose selected cool bed sites with a substrate that was moist, wet or had standing water, and avoided bedding in open or sparse vegetation. On warm days and during the warmest periods of the day, moose increased selection for wet substrate and for bed sites in standing water with sparse vegetation, which they avoided on cool days and during cool periods of the day. Strong and context-dependent selection for bed sites that would reduce heat gain and ameliorate heat load supports the notion that bed sites are a thermal refuge and a way to behaviourally mitigate warming temperatures. Flexibility in habitat selection may be a primary way for large endotherms to combat a warming climate, although doing so is contingent on habitat assemblages that offer thermal refuge to limit heat gain and importantly, facilitate heat loss. Highlights: Moose select bed sites with wet ground or standing water to mitigate heat loads. Canopy cover was not an influential factor in bed site selection. Heat loss is more important for behavioural thermoregulation than limiting heat gain. Flexibility in bed site selection may be a way for endotherms to combat warming. Selection of wet ground increased on warm days and during the warmest diel periods.